Melancholia, choroba, szaleństwo – kompleks staropolskiego poety metafizycznego: idee, inspiracje, motywy, postawy - Fischer, Jakub (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
This article tends to analyse the problems concerning the reception of ancient theory of melancholia, especially in renaissance and early Baroque literary studies. The melancholia as disease, habit, fear, cognition, meditation, inspiration and sin, is also very inspiring idea, allowing to understand the essence of Old Polish metaphysical poetry, in particular the complex of metaphysical poet – his behaviour, reasons, inspirations and attitudes.
Melancholia, disease, madness – the complex of Old Polish metaphysical poet: ideas, inspirations, motifs, attitudes
On the basis of the sixteenth and seventeenth-century discussions about the poetic inspiration, the poet’s mental state, developed naturalistic and psychological ideas of poetic madness, categorizing a state of mind, soul, and imagination of the poet. The source for these considerations were primarily Aristotle’s writings and theories, concepts, moreover theories of four humors and four temperaments. Among the theoreticians of the Renaissance and Baroque literature, in the thoughts of madness (as a form of poetic and divine madness, mania, enthusiasm) central gained concept of melancholia. The form of melancholia was useful to explain, define and classify a number of phenomena relating to madness in a wide mental, somatic and symbolic dimension. A very interesting interpretation of the melancholia presented polish philosopher and translator Sebastian Petrycy. In his translation and appendages to the Aristotle’s Nicomachean Ethics (Przydatki do Etyki Arystotelesowej, 1618) melancholy is defined, based on the ancient idea, as a source of both wit and wisdom (as a gift from God) and madness (Dionysian, divine, poetic and erotic). The early Baroque theory of melancholia can be useful to understand and analyse Old Polish metaphysical poetry (Rymy duchowne of Sebastian Grabowiecki and metaphysical poems of Kasper Twardowski). In Old Polish metaphysical poetry there is full of ideas, themes, motifs and symbols coincide with the concept of melancholia. The idea of melancholia allows us to understand more deeply characteristic and specific topics of metaphysical poetry (sin / disease / distress / madness), themes (poet / madman / prophet), ideas (madness and loss of sense as an introduction to meditation) and attitudes (poet experienced by the symbolic, mythical, real and fictional madness). The problem of melancholia allows us to specify an unusual phenomenon – the complex of metaphysical poet – to understand a man who was “distraught”, a man “poisoned”, homo (poeta) melancholicus.
Keywords: lyric poetry; sin; Old Polish metaphysical poetry; ancient tradition; reception studies; Baroque; renaissance tradition; melancholia; melancholy disease; melancholy habit; mania; saturnine; four humors; four temperaments; black bile